Educate the verse. (Journal of Parents and Teachers, 2014)
Poetry lives, but is in danger of extinction. That is why UNESCO has decreed March 21st as World Poetry Day. Parents and Teachers also bet on poetry.
Keywords: Poetry; World Poetry Day.